The influence of the human development index on domestic investment flows in Indonesia - Widjajanto, Tulus; Hapsari, Vinandri (Jurnal Konseling dan Pendidikan, 2025)
This study examines the influence of the Human Development Index (HDI) on domestic investment flows in Indonesia using a qualitative research approach. By employing a literature review and library research method, this paper synthesizes existing studies to understand how human development indicators—such as education, health, and income—affect investment decisions within the country. The findings suggest that regions with a higher HDI tend to attract more domestic investment due to better infrastructure, a more skilled workforce, and improved economic stability. Conversely, areas with lower HDI scores often struggle to secure substantial investment due to inadequate human capital and limited access to resources. Furthermore, this study highlights the role of government policies in bridging the development gap, emphasizing the importance of targeted investments in education and healthcare to foster sustainable economic growth. The analysis also considers the potential challenges faced by investors in different regions of Indonesia, including regulatory constraints, market uncertainties, and socio-economic disparities. By drawing insights from various academic sources, this research contributes to the broader discourse on the relationship between human development and economic activity, particularly in emerging economies. The study concludes that a strong HDI serves as a crucial determinant for enhancing domestic investment flows, thereby reinforcing the need for continuous improvements in human capital development. Future research should explore empirical data to further validate these qualitative findings and provide more policy-oriented recommendations.